Considerations for Selecting a Bull - Martha Thomas; Matt Hersom (EDIS)
AN218, a 3-page fact sheet by Martha Thomas and Matt Hersom, lists factors to consider for selecting a bull, one of the largest decisions dictating carcass merit for the subsequent calves. Includes references. Published by the UF Department of Animal Sciences, June 2009.